MATRICIAMENTO COMO ARRANJO DE GESTÃO COMPARTILHADA EM SAÚDE MENTAL: PERCEPÇÕES DOS PROFISSIONAIS DA ATENÇÃO PRIMÁRIA À SAÚDE NO MUNICÍPIO DE CAMPO GRANDE/MS - GUILHERME ARTHUR FATINI MOREIRA (2023)
Mental disorders are among the main causes of morbidity in Brazil and the world, depression alone accounts for more than 4% of the global burden of disease and occupies a prominent place among the main causes of disability, contributing to general health problems, such as acute myocardial infarction, diabetes and premature death. Individuals with mental disorders exhibit higher rates of disability and mortality, with reduced life expectancy when compared to the general population. Primary Health Care is recognized as the main gateway into the Unified Health System, playing a role in coordinating care in the network; when the concepts of specialized care are integrated into Primary Care, a new concept appears introduced in 1999 by Gastão Wagner de Souza Campos called Matriciamento, which aims to provide specialized assistance support and jointly build a pedagogical-therapeutic intervention project integrating the different assistance levels. The research aimed to understand the perceptions of Primary Health Care professionals in relation to Matrix Support in Mental Health, describing the theory and process of matrix support in Primary Health Care, investigating the concept and principles of matrix support from the perspective of Care professionals. Primary Health Care, analyzing the work process in Primary Health Care and its integration with the Psychosocial Care Network, identifying the facilitating factors and barriers to Matrix Support and describing how the integration between mental health and Primary Health Care can contribute for the promotion and protection of the health of individuals with mental disorders. For this, a qualitative approach was adopted carried out in Campo Grande-MS, between November and December 2021. The study sample adopted an intentional non-probabilistic approach by saturation, composed of health professionals working in Family Health Units, who were selected according to their performance in the Family Health Strategy and carry out Matrix Support activities. The composition of the study participants included all professionals involved in Matrix Support of the reference teams from four Primary Health Care units. Data collection was carried out through a script of questions directed to focus groups made up of 11 to 14 participants, and for each group, the questions introduced initially were easy to answer, progressively increasing the specificity and complexity. The researcher was responsible for moderating the discussion, which enabled a certain adaptability in the management of the group, recording pertinent issues that had not been anticipated. The interviews were recorded, preserved in digital formats and fully transcribed for evaluation. To organize the collected material, the Discourse Analysis method was used, an aspect of the French matrix of this discipline, which conceives discursive objects under the tension of historicity, interdiscursivity and systematicity of the language. It was understood from the perceptions of Primary Health Care professionals that there are divergences in knowledge and approaches adopted between different health units, so that participants demonstrate theoretical knowledge in relation to matrix support in accordance with the originally methodological process proposed, the concepts and practical principles are not in accordance with the principles of Primary Health Care nor with the Matrix Support model. This discrepancy highlights the importance of a preliminary situational diagnosis in the territories and in the Psychosocial Care Network before implementing matrix support, in order to understand the needs of the teams and establish realistic expectations of the expected results for better effectiveness of future practices, aiming at comprehensive health care. of the population. This work has the potential to significantly impact the quality of healthcare services by exploring the collaborative working approach between different healthcare teams and professionals; Research can provide important support to improve the progression and effectiveness of care at the primary health care level. Furthermore, the applicability of the content of this study can contribute to improving patient care, optimizing human resources and promoting an integrated approach to health in the community served by Family Health Strategies.